PENGARUH EKSPOR, IMPOR, INFLASI, DAN KEBIJAKAN ACFTA TERHADAP CADANGAN DEVISA ASEAN-5 PERIODE 2005 – 2019 - Apriadi, Gusti Ngurah Sukma; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022, 2022)
To overcome obstacles in international trade, several countries have made bilateral and multilateral agreements that can benefit both parties, one of which is the ASEAN – China Free Trade Agreement (ACFTA). State foreign exchange is one source of foreign trade financing. Several factors that affect foreign exchange reserves are export and import activities, and inflation. With the ACFTA policy, it is expected to facilitate international trade activities in ASEAN-5 countries so as to increase the growth of the country's foreign exchange reserves. The purpose of this study is to analyze the effect of exports, imports, inflation, and ACFTA policies on ASEAN-5 foreign exchange reserves for the period 2005 – 2019. The analysis is carried out using panel data regression, using secondary data sourced from the World Bank and the World Trade Organization. The results of the analysis show that exports, imports, inflation, and ACFTA policies simultaneously have a significant effect on foreign exchange reserves of ASEAN – 5. 2005-2019. The import variable (X2) partially has a positive and significant effect on foreign exchange reserves before and after the enactment of ACFTA in ASEAN-5 for the period 2005-2019. The inflation variable (X3) partially has a significant negative effect on foreign exchange reserves before and after the enactment of ACFTA in ASEAN-5 period 2005-2019. The ACFTA policy variable (D1) partially has a significant effect on foreign exchange reserves before and after the establishment of ACFTA in ASEAN-5 for the 2005-2019 period.